Sparsentan for Focal Segmental Glomerulosclerosis in the DUET Open-Label Extension: Long-term Efficacy and Safety - Campbell, Kirk N; Gesualdo, Loreto; Murphy, Edward; Rheault, Michelle N; Srivastava, Tarak; Tesar, Vladimir; Komers, Radko; Trachtman, Howard (Kidney medicine, 2024)
RATIONALE & OBJECTIVE: Sparsentan is a novel, non-immunosuppressive, single-molecule, dual endothelin angiotensin receptor antagonist (DEARA) examined in the ongoing phase 2 DUET trial for focal segmental glomerulosclerosis (FSGS). In the DUET 8-week double-blind period, sparsentan resulted in greater proteinuria reduction versus irbesartan. We report the long-term efficacy and safety of sparsentan during the open-label extension over more than 4 years. STUDY DESIGN: Patients were examined from their first sparsentan dose (double-blind period or open-label extension) through 4.6 years. SETTING & PARTICIPANTS: Patients with FSGS, excluding secondary FSGS. INTERVENTION: Sparsentan (200, 400, and 800 mg/d). OUTCOMES: Urinary protein-creatinine ratio, FSGS partial remission endpoint (urinary protein-creatinine ratio ≤1.5 g/g and >40% reduction from baseline), estimated glomerular filtration rate, and blood pressure approximately every 12 weeks. Treatment-emergent adverse events by year and cases/100 patient-years. RESULTS: 109 patients were enrolled; 108 received ≥1 sparsentan dose; 103 entered the open-label extension (68 sparsentan, 35 irbesartan during the double-blind period). Sparsentan was ongoing in 45/108 patients (41.7%); median time to treatment discontinuation was 3.9 years (95% CI, 2.6-5.2). Mean percent proteinuria reduction from baseline was sustained through follow-up. Achieving partial remission within 9 months of first sparsentan dose (52.8% of patients) versus not achieving (47.2%) was associated with significantly slower rate of estimated glomerular filtration rate decline over the entire treatment period (-2.70 vs -6.56; P = 0.03) and in the first 2 years (-1.69 vs -6.46; P = 0.03). The most common treatment-emergent adverse events (>9 cases/100 patient-years) were headache, peripheral edema, upper respiratory infection, hyperkalemia, and hypotension. Peripheral edema and hypotension declined from year 1 (13.9% and 15.7% of patients, respectively) to ≤4% in years ≥2. There were no cases of heart failure and no patient deaths. LIMITATIONS: The open-label extension does not include a comparison group. CONCLUSIONS: Long-term sparsentan treatment showed sustained proteinuria reduction and a consistent safety profile.